If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 5) + -6 = 16 Reorder the terms: 2(5 + x) + -6 = 16 (5 * 2 + x * 2) + -6 = 16 (10 + 2x) + -6 = 16 Reorder the terms: 10 + -6 + 2x = 16 Combine like terms: 10 + -6 = 4 4 + 2x = 16 Solving 4 + 2x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2x = 16 + -4 Combine like terms: 4 + -4 = 0 0 + 2x = 16 + -4 2x = 16 + -4 Combine like terms: 16 + -4 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| -15=x+(-16) | | X-Y+A=3 | | X-Y+Z=3 | | x-2/12=5/6 | | -1+y/8=15 | | 4x+8y+20= | | 3x^3-7.5x^2-32=0 | | -3+m/9=10 | | -10=-2+1/2d | | 158-3x=24x+20 | | 6-7x=51-42x | | X-Y+C=3 | | 2x^2-1=9 | | 76-2x=10x-2x | | 12x-4=4x-3 | | 3y+4=7-4y | | 2(2x+7)+3(x+2)=5(x-1)-1 | | 6x-8=2x+32 | | 1+8x=22x+x | | 8y-2=7+6y | | (2x/3)=(4/7) | | 9x-1+8z-7x+z=0 | | 2x^2+17xy+8y^2= | | 8(2x+1)=11x+53+5x | | -x+9=x-21 | | x+9=x-21 | | x/9=40/5 | | 2x+1=x^2-14x+49 | | 5x+46=x^2+16x+64 | | 36=2x*3y | | x^2+4x+4+14x+28+45=0 | | 7(x-2)=-6+9x |